Effect of FDI inflows on employment generation in selected ECOWAS countries: Heterogeneous panel analysis - Timothy Ayomitunde Aderemi; Olawunmi Omitogun; Bukonla G. Osisanwo (CBN Journal of Applied Statistics, 2022)
The aim of this study is to examine the effect of FDI on employment in ECOWAS sub region between 1990 and 2019. The study utilizes a panel autoregressive dis- tributed lag model to analyze the short run and long run relationship between FDI and employment across ECOWAS sub region. In the short run, the impact of FDI on employment is negative and statistically not significant. Meanwhile, in the long run FDI has a positive and statistically significant impact on employment rate. This implies that FDI has the capacity to generate employment in countries in ECOWAS sub region. Therefore, this study recommends that policymakers in the ECOWAS sub region should facilitate the achievement of productive, employment and decent work for all, policy measure that will facilitate the inflows of FDI should be embarked upon.
Keywords: F21; F23; F36; J21; J23; 330; FDI; employment; ECOWAS; Panel ARDL